(
2
x
−
3
)
(
x
2
−
x
−
2
)
Factor
x
2
−
x
−
2
using the AC method.
Tap for fewer steps...
Factor
x
2
−
x
−
2
using the AC method.
Tap for more steps...
(
2
x
−
3
)
(
(
x
−
2
)
(
x
+
1
)
)
Remove unnecessary parentheses.
(
2
x
−
3
)
(
x
−
2
)
(
x
+
1
)
The answer is B because -3 -8 = -11.
Easy, it says "for ANY positive integer" so just test any positive integer
remember that n! means times all integers from 1 to that number n
lets try 1
(1+1)!/(1!)-1=
(2!)/(1!)-1=
2/1-1=
2-1=
1
if you don't believe me, try 2
(2+1)!/(2!)-2=
(3!)/(2!)-2=
(6)/(2)-2=
3-2=
1
te answer is 1, B
and number 9
easy, remember the exponential law
(x^m)(x^n)=x^(m+n)
jsut add the exponents
first gropu like bases
(r^2r^2/3)(t^1/2t^-3/2)
add bases
(r^2 and 2/3)(t^-1)=
(r^2∛(r^2))(1/t)=
Answer:
4 widgets
Step-by-step explanation:
8÷2=4
Mark me brainliest